Ambiguity tolerance in organizations: definitional clarification and perspectives on future research - McLain, David L.; Kefallonitis, Efstathios; Armani, Kimberly (Frontiers in Psychology, 2015)
Ambiguity tolerance is an increasingly popular subject for study in a wide variety of fields. The definition of ambiguity tolerance has changed since its inception, and accompanying that change are changes in measurement and the research questions that interest researchers. There is a wealth of opportunity for research related to ambiguity tolerance and recent advances in neuroscience, measurement, trait research, perception, problem solving, and other fields highlight areas of interest and point to issues that need further attention. The future of ambiguity tolerance research is promising and it is expected that future studies will yield new insights into individual differences in reactions to the complex, unfamiliar, confusing, indeterminate, and incomplete stimuli that fall within the conceptual domain of ambiguity.